AethelmE, HTML5 Game Engine with Multiple Canvas Elements - Kevin Gunawan; Raymond Bahana (Bina Nusantara University, 2016)
Game engine is software which ease the game development. As the processor power technology evolved and the HTML5 (HyperText Markup Language 5) specification are developed, browsers nowadays can natively (without any need for external plug-in) display animations and multimedia files (audio and video) using JavaScript as the programming language. Some of the features which are used in this research are HTML5‘s canvas and audio elements. The problem is that none of the existing free HTML5 game engines is able to support multiple canvas elements. This research will create a game engine, called AethelmE, which support multiple canvas elements as its unique feature. This game engine is also able to support sprite transformation, browsers compatibility, external asset loading, and audio format compatibility. This research successfully resulted in creating an HTML5 game engine which supports multiple canvas elements. It also supports all the scopes, with a small exception on sound format compatibility. Moreover, this research conducted a performance comparison testing of multiple HTML5 game engines, from which can be concluded that multiple canvas elements does not give significant performance gain compared to a single canvas.